Silicon carbide power device characteristics, applications and challenges: an overview - Muhamad Faizal Yaakub; Mohd Amran Mohd Radzi; Faridah Hanim Mohd Noh; Maaspaliza Azri (Institute of Advanced Engineering and Science, 2020)
Silicon (Si) based power devices have been employed in most high power applications since decades ago. However, nowadays, most major applications demand higher efficiency and power density due to various reasons. The previously well-known Si devices, unfortunately, have reached their performance limitation to cover all those requirements. Therefore, Silicon Carbide (SiC) with its unique and astonishing characteristic has gained huge attention, particularly in the power electronics field. Comparing both, SiC presents a remarkable ability to enhance overall system performance and the transition from Si to SiC is crucial. With regard to its importance, this paper provides an overview of the characteristics, advantages, and outstanding capabilities in various application for SiC devices. Furthermore, it is also important to disclose the system design challenges, which are discussed at the end of the paper.